Novel mutation of COG5 in a Taiwanese girl with congenital disorders of glycosylation manifesting as developmental delay - Yu-Chi Wang; Dau-Ming Niu; Li-Zhen Chen; Yun-Ru Chen; Chia-Feng Yang (Molecular Genetics and Metabolism Reports, 2024)
We are documenting the case of An 11-year-old girl who has been followed up at our out-patient clinic since birth with clinical presentations including intrauterine growth restriction, recurrent periodic fever in infancy, hypotonia, global developmental delay, liver function impairment with cirrhotic changes, and clinodactyly. Congenital abnormalities were suspected but a series of examinations including brain MRI, liver biopsy and muscle biopsy yielded insignificant findings. Whole genome sequencing (WGS) was conducted and revealed three novel mutations (c2T > G, c1826T > C, c.556–560delAGTAAinsCT) of the COG5 gene. A diagnosis of COG5-congenital disorders of glycosylation (COG5-CDG, or CDG IIi), with neurologic presentation was established. Sanger sequencing in the patient and her parents confirmed the compound heterozygous mutation. Upon literature review, we identified the patient as the first case of COG5-CDG in Taiwan. Our study enhances the clarity of the correlation between the mutative genes and the presentation of COG5-CDG.